Cinema e aprendizagem histórica: potencialidades do filme “O Tronco” (1999) no ensino de história regional - Silva , Wanderson Cláudio da (2024)
This paper proposes a reflection on cinema as an enriching tool for the educational environment, highlighting its application in the classroom. The approach adopted is based on a methodology grounded in the analysis of the film "O Tronco" (1999), by João Batista de Andrade, as a research source, exploring its relevance as a resource for historical understanding. The research incorporates theories that examine the importance of cinema in historical context, emphasizing the contribution that this form of media can provide, especially when films present interpretable characteristics from a regional/local perspective. As part of the study, we highlight the relevance of theorists dedicated to analyzing the role of cinema in historical construction. Furthermore, we address the ability of films to capture specific cultural nuances, enriching the process of historical learning. In conclusion, we have developed a comprehensive guide that offers guidance for understanding, using, and creating educational activities based on the analysis of specific scenes from the film "O Tronco." This guide aims to provide educators with a practical tool to effectively integrate cinema into the teaching environment, promoting a more engaging and contextualized approach to historical learning.